Life form and Chorological types spectrumof Succulent plants inWadi Yabraq and its around, Al-Wadheia, Abyan Governorate-Yemen (Al-Mukhtar Journal of Basic Sciences, 2026)
The present study was based on extensive surveys and field observation of the diversity of succulent plants in Wadi Yabraq and it’s around, Alwadheea Dist. In the present investigation, it is observed about 71 Species belonging to 37genera and 21 Families were identified. Most of families of plants that contributed in the investigated area were Apocynaceae and Euphorbiaceae. Analysis of the habit shows that Shrubs are dominat with 31 species followed by herbs with 29 species, Trees with 8 species, Liana with 3 species. Investigation of life forms species shows that Chamaephytes are the most important. (49.30%), followed by Therophytes (18.30%), phanerophyte (16.90%) HemicryptophyteS (8.45%) ,Geophytes (4.22%). Among the common regions vegetative, Sudano–Zambezian, were with the highest followed by Endemic and (Sudano–Zambezian Saharo–Arabian).